(untitled) (Research, Society and Development, 2023)
Described as a process inherent to all living beings, aging is characterized by the loss of adaptability, as well as the organic and functional decline of the individual. Therefore, this study aims to investigate and compare the extent to which regular physical activity helps to minimize the problems inherent to old age with regard to attention and information processing in elderly people who practice and do not practice regular physical activity, analyzing three attentional variables: attentional speed, attentional accuracy and resistance to fatigue. The research was carried out with a sample of 30 participants organized into two distinct groups, the first group was composed of practitioners of physical activity and the other group of non-participants. As an instrument for data collection, the Toulouse-Piéron attention test was applied equally to both groups. The results found indicated that the group practicing regular physical activity had higher levels in the three variables evaluated, thus revealing the importance of physical activity in improving and maintaining the attention of people in the aging process. It is concluded that physical activity is an important component in improving the maintenance of elements related to information processing in elderly people.